Zachowania suicydalne jako przejaw zachowań patologicznych - Migała, Paweł (Józefów: Wyższa Szkoła Gospodarki Euroregionalnej)
This overview presents the significant findings on suicidal risk in children and adolescents. Specifically, it outlines macroscopic Romains of suicidal youth such as psychosocial, sociocultural, and philosophical features. A definition of youth suicidal episodes and descriptions of their component features are offered. Risk factors involving psychopathology in the suicidal youngster and family as well as other environmental, developmental, and physiological stresses are highlighted. Directions for clinical management and empirical research are offered. Suicidal behaviour is an action intended to harm oneself and includes suicide gestures, suicide attempts, and completed suicide.
Keywords: samobójstwo; dziecko; psychologia; sucide; child; psychology